2022
DOI: 10.1093/plcell/koac239
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Rab protein RABC1 affects stomatal development by regulating lipid droplet dynamics

Abstract: Lipid droplets (LDs) are evolutionarily conserved organelles that serve as hubs of cellular lipid and energy metabolism in virtually all organisms. Mobilization of LDs is important in light-induced stomatal opening. However, whether and how LDs are involved in stomatal development remains unknown. We show here that Arabidopsis thaliana LIPID DROPLETS AND STOMATA 1 (LDS1)/RABC1 (At1g43890) encodes a member of the Rab GTPase family that is involved in regulating LD dynamics and stomatal morphogenesis. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 127 publications
0
13
0
Order By: Relevance
“…The analysis suggested that the phenotype of dsm1 mutant was caused by a recessive mutation of a single unknown gene. Therefore, dsm1 was selected for mutant gene cloning as described (He et al ., 2018; Lukowitz et al ., 2000; Ge et al ., 2022). Totally, 800 dsm1 phenotype seedlings were identified for fine gene mapping.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis suggested that the phenotype of dsm1 mutant was caused by a recessive mutation of a single unknown gene. Therefore, dsm1 was selected for mutant gene cloning as described (He et al ., 2018; Lukowitz et al ., 2000; Ge et al ., 2022). Totally, 800 dsm1 phenotype seedlings were identified for fine gene mapping.…”
Section: Methodsmentioning
confidence: 99%
“…Stomatal apertures were measured as described (Geisler et al ., 2000; Ge et al ., 2022). Briefly, attach the abaxial side of the leaflet with light‐bodied vinylpolysiloxane dental resin (Elite HD+, Zhermack Clinical, Italy) and then remove it as soon as it dried.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When LD production is induced by oleic acid, SEIPIN2/3 is mainly located on the LD surface in wild-type, while very little SEIPIN2/3 was located on the LD surface in RABC1 mutants. Thus, together with its partner GEF, RABC1 negatively controls the dynamics and size of LDs in young stomata by regulating the localization of its effector factors SEIPIN2/3 [ 13 ].…”
Section: Other Proteins and Factors Involved In Ld Formationmentioning
confidence: 99%
“…Homologs of some regulatory proteins related to animal LD formation have been identified in plants, however, there is no experimental evidence to show whether they function the same way in plant LD formation [ 11 , 12 , 13 ]. It has been shown that plant and animal LD surface proteins are completely different ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%